The Essence of Family Planning in Islam: Achieving Family Well-Being Through Maqashid Shariah - Fauzi, Ahmad; Zikri, Ahmad; K, Hendri; Agustar, Armi (State of Islamic Institute Langsa, 2024)
Ideally, family planning (FP) is considered important for maintaining family well-being. However, in reality, there are still many negative views in society that oppose the practice of FP, even causing problems in its implementation. This article falls under library research with a qualitative approach. The methodology used is descriptive analysis, specifically explaining the meaning and essence of FP in the context of family well-being through the analysis of Maqasid Shariah theory. The results of the study indicate that FP plays a significant role in family well-being, especially for young couples who have recently married. Mental and financial preparation before educating and caring for children becomes a key factor in maintaining family stability. In the context of Maqasid Shariah, FP actively contributes to preserving health, lineage, wealth, life, and even religion.